Nucleolar coefficient of granulocyte precursors and granulocytes after visualization of nucleoli by two different methods - Likovský, Z; Smetana, K (Acta histochemica, 2000)
To clarify differences in the incidence and number of nucleoli in the granulopoietic lineage, these nuclear components were studied in human and rabbit granulocyte precursors and granulocytes after visualization by 2 widely employed cytochemical procedures, i.e. a procedure for the demonstration of RNA and the silver reaction for the demonstration of nucleolar silver stainable proteins (SSPs). In early stages of the granulocyte proliferating compartment, substantial differences were not found between specimens in which nucleoli were visualized by both procedures. However, in contrast to specimens stained with the silver reaction, the number of cells without nucleoli was substantially larger in advanced stages of granulocyte development in specimens stained for RNA. The number of nucleoli per cell as expressed by the nucleolar coefficient was generally larger in specimens stained with the silver reaction for nucleolar SSPs. These differences were significant starting with the stage of myelocytes. Moreover, in specimens stained with the silver reaction, most of human mature granulocytes did not contain nucleoli but nucleoli were present in all mature granulocytes of rabbits. Such differences were not observed in specimens stained for RNA in which most granulocytes were without RNA-containing nucleoli. Thus, the evaluation of the presence or absence of nucleoli in specimens depended on the visualization procedure. It is likely that in micronucleoli which are characteristic for terminal differentiation of the granulocytic lineage, RNA-containing structures may be lost or are below the detection limit of the light microscope. In addition, differences in the presence of nucleoli exist apparently between human and rabbit granulocytes in specimens stained for SSPs but not in those stained for RNA.
Keywords: hematopoetické kmenové buňky; Hematopoietic Stem Cells; zvířata; králíci; Silver Staining; buněčné jadérko; granulocyty; Nucleolus Organizer Region; Animals; lidé; Rabbits; barvení stříbrem; Male; Nuclear Proteins; Granulocytes; jaderné proteiny; Humans; mužské pohlaví; RNA; organizátor jadérka; Cell Nucleolus